Women’s empowerment and food security in the South-South geopolitical zone of Nigeria - Oghuvbu, Ejiroghene Augustine (Faculty of Social and Political Science, Universitas Airlangga, 2024)
The study investigated the linkage between food security and women’s empowerment in Nigeria’s South-South geopolitical zone. In the South-South geopolitical zone of Nigeria, 300 respondents participated in a cross-sectional survey designed utilising a method known as non-probability sampling to collect the data. Data analysis in this study used a linear regression test with the help of SPSS version 23 software. The study found food security and women’s empowerment are linked in a substantial way. The study found that in Nigeria’s South-South geopolitical zone, women’s empowerment has a positive and statistically significant impact on food security. It also demonstrated how food security might result from the empowerment of women in the South-South geopolitical zone of Nigeria in terms of agricultural output and distribution. From the research findings, the study suggests that to improve the situation government policy on agriculture it is imperative to prioritise the advancement of women, since doing so will enhance their standing and boost agricultural output in Nigeria. Apart from that, legislative changes are also needed regarding easy access to resources, and government investment in rural women’s education and health.